Long-Term PAE Results: What Do We Know - Bilhim, Tiago (Seminars in Interventional Radiology, 2022)
Prostatic artery embolization (PAE) is a minimally invasive technique with proven safety and efficacy to treat lower urinary tract symptoms (LUTS) due to benign prostatic obstruction (BPO) or benign prostatic hyperplasia (BPH). In this review, we discuss the required level of evidence to implement and adopt treatment options for patients with LUTS due to BPO/BPH. Focus is given on the long-term (>3 years) data after PAE with reported outcomes including cohort sizes, follow-up times, reintervention rates (repeat PAE and prostatectomy), need for LUTS/BPO medical therapy, and improvements in International Prostate Symptom Score/quality of life score, peak flow rate (Qmax), postvoid residual, prostate volume, and prostate-specific antigen. The durability of treatment effects after PAE and need for prostatic reinterventions need to be taken into consideration when discussing treatment options with patients and referring colleagues from other medical specialties. Developments in medical devices used for PAE have allowed for a continuous drop in unilateral PAE rates over the last 12 years and will probably play a role in optimizing technical and thus clinical outcomes for patients with LUTS due to BPH/BPO.
Keywords: long term; prostatic artery embolization; lower urinary tract symptoms; benign prostatic obstruction; benign prostatic hyperplasia; interventional radiology